Optimalisasi Penerapan Alokasi Dana Desa dalam Upaya Meningkatkan Pendapatan Desa Gambus Laut Kab. Batu Bara - Aini, Nur; Hasugian, Hotbin (Journal Research of Economic and Bussiness, 2025)
This study aims to determine the program for implementing village fund allocation in increasing village income, as well as optimizing village fund allocation as an effort to increase village income, as well as optimizing village fund allocation as an effort to increase village income. Data collection techniques in this study used interview and documentation techniques. The results of the research that researchers have conducted indicate that the program for implementing village fund allocation in gambus laut village are infrastructure development, natural resource development and financial counseling, community empowerment, monitoring and evaluation and development of the agricultural sector. Optimizing village fund allocation in an effort to increase gambus laut village income is mapping village potential, developing the agricultural and fisheries sector, improving tourism infrastructure, empowering village communities and institutions, collaborating with the private sector, and financial institutions, preparing long-term development, monitoring and evaluation. The optimization of the utilization of village fund allocation in gambus laut has been maximally allocated for the implementation of village government policies in increasing village income and shows that in the planning process, the village government has implemented every rule that has been set. Regarding the improvement of the quality of the utilization of village funds themselves, community contributions are important to control the policies of village authorities so that they show benefits for the entire community. Keyword: Village Fund Allocation Program, Optimization, Village Fund Allocation